Evaluation of the Impact of Pistacia atlantica Desf. Oleo-gum Resin on Complete Freund’s Adjuvant-induced Arthritis in a Wistar Rat Model - Toofan, Mobina; Pour, Pardis Mohammadi; Kiani, Amir; Fakhri, Sajad; Farzaei, Mohammad Hosein (Letters in Drug Design & Discovery, 2024)
BackgroundPistacia atlantica Desf., also known as Atlantic pistachio or Mt. Atlas mastic tree, has been used in traditional medicine for its anti-inflammatory properties, helping to reduce inflammation in conditions like arthritis. Additionally, the tree's resin possesses antioxidant properties that can help protect against oxidative stress.The anti-arthritic efficacy of Pistacia atlantica oleo-gum resin extract (PAG) remains unvalidated, as its potential therapeutic benefits have not been substantiated. In the current investigation, we have substantiated the inhibitory properties of the PAG in mitigating the development of rheumatoid arthritis induced by Complete Freund's Adjuvant in rats.MethodsMale Wistar rats weighing 160±10 g were subjected to immunization through intradermal injection of 0.1 mL of Complete Freund's Adjuvant (CFA) into the left hind metatarsal footpad. Following the induction of adjuvant arthritis, oral administration of PAG was initiated at doses of 10, 400, and 800 mg/kg once a day. Prednisolone (10 mg/kg, daily) was employed as a positive control in this study. Various parameters, including paw swelling, arthritic index, body weight loss, spleen index, thymus index, serum cytokines, inflammatory mediators, and histological alterations, as well as nitrite glutathione and catalase level, were measured. Furthermore, the expression and activity of matrix metalloproteinase (MMP)-2 and MMP-9 were evaluated.ResultsPAG exhibited noteworthy efficacy in attenuating paw swelling and reducing the arthritic index. Moreover, it resulted in enhanced body weight loss and a consequential reduction in the thymus index. PAG (400mg/kg) significantly decreased the level of serum nitrite in the intervention group, as well as the levels of serum glutathione. On the other hand, catalase activity increased, the activity of MMP-9 decreased, and the level of MMP-2 increased compared to the intervention group. The histopathological results revealed that PAG (at doses of 400 mg/kg) had the best therapeutic effects.ConclusionIn conclusion, the present study confirms the anti-arthritic activity of PAG in rats. The extract of PAG was found to prevent rheumatoid arthritis induced by Complete Freund's Adjuvant, as evidenced by the significant suppression of paw swelling and arthritic index.
Keywords: DMARDs